2011
DOI: 10.1111/j.1600-0897.2011.01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Interleukin-6, Interleukin-1β and Human Chorionic Gonadotropin in Pre-eclampsia

Abstract: Our results highlight the inflammatory origin of PE and reinforce the possible role of hCG in the complex aetiology of its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 45 publications
4
67
2
2
Order By: Relevance
“…CXCR3 is preferentially expressed on Th1 cells and CCR4 on Th2 cells, thus further amplifying Th1 and Th2 immunity, respectively (27). Although several previous studies by us and by others have shown a Th1-like pattern of cytokines in preeclampsia, some of them have been rather small and in general they were not controlled for gestational age and cortisone treatment, commonly used in EOP (12,21,(29)(30)(31)(32). As other studies have failed to show differences in levels of cytokines between normotensive and pre-eclamptic pregnancies (20,33,34), the previous results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR3 is preferentially expressed on Th1 cells and CCR4 on Th2 cells, thus further amplifying Th1 and Th2 immunity, respectively (27). Although several previous studies by us and by others have shown a Th1-like pattern of cytokines in preeclampsia, some of them have been rather small and in general they were not controlled for gestational age and cortisone treatment, commonly used in EOP (12,21,(29)(30)(31)(32). As other studies have failed to show differences in levels of cytokines between normotensive and pre-eclamptic pregnancies (20,33,34), the previous results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Ez a sajátosság biztosítja a magzat egészséges fejlődését a kedvező immunológiai környezet kialakítása révén [20]. A praeeclampsiával szövődött terhességek-ben ugyanakkor a proinfl ammatorikus citokinek (IL-1β, IL-6, IL-8, TNF-α) magasabb szérumszintje fi gyelhető meg, amely az antiinfl ammatorikus citokinek csökkené-sével is együtt jár [21,22]. A proinfl ammatorikus citokinek fokozott termelődése valószínű, hogy kulcsfontossá-gú szerepet tölt be a praeeclampsia patofi ziológiájában [23].…”
Section: öSszefoglaló Közleményunclassified
“…12 Many researchers had found that the plasma level of IL-1β was elevated in preeclamptic women. 9,[13][14][15] And increased placental expression of IL-1β was also observed in several researches. 13 IL-1β is located in 70-110 kb region of chromosome 2q13-21, including 7 exons and 6 introns.…”
Section: Introductionmentioning
confidence: 99%
“…The serum level of inflammation cytokines, one kind of cytokines, such as IL-1β, IL-2, IL-6 and IFN-c had been found to be higher in women with PE than in normotensive pregnant women, [7][8][9] which leaded to harmful Th1 immunity, threatening pregnancy by generating cytotoxic factors that injured maternal endothelium, altered steroid hormones biosynthesis and affected other factors which were implicated in trophoblast invasion and maternal spiral artery remodeling. 10,11 The production of inflammatory cytokines is regulated by the cytokine gene, thus, the cytokines gene polymorphism may play a key role in the development of PE.…”
Section: Introductionmentioning
confidence: 99%